FREKUENSI KEHAMILAN BERHUBUNGAN DENGAN KEJADIAN ABORTUS - Budi Astyandini; Tri Nurhidayati (Midwifery Care Journal, 2021)
Bleeding is one of the causes of maternal death. Bleeding before the start before the 1st trimester caused by hydatidiform mole, interrupted ectopic pregnancy and abortion. The cause of abortion from maternal faktors is the main faktor causing the abortion. The purpose of this study was to determine the relationship between the frequency of pregnancy and the incidence of abortion in pregnant women. This research is a descriptive correlative study with a population of all pregnant women at Patean Health Center with a total sample of 26 people. The data used were secondary data using an observation sheet in the form of a checklist with univariate and bivariate analysis of the chi-square test at a value of p 0.05. The results showed that there was a relationship between abortion and the frequency of pregnancy and the incidence of abortion p = 0.027. It is recommended that midwives provide more focus on multigravida pregnant women through early detection of pregnancy complications through integrated ancillary services.